An open label study to assess the efficacy of ceftiofur in treatment of clinical mastitis in buffaloes - Boora, Ashok; Yadav, Sarita; Devi, Parvina; Singh, Kunwar Pal; Cheema, Pawanjit Singh; Muley, Vijay; Sehrawat, Virender; Dhamanaskar, Ketan; Singh, Inderjeet (Buffalo Bulletin, 2021)
The study objective was to evaluate the efficacy of Ceftiofur hydrochloride intramammary (IMM) formulation (Spectramast LC, Zoetis India) with or without parenteral Cefoperazone/Sulbactum antibiotic on bacteriological cure, clinical cure and pathogen cure in lactation clinical mastitis (CM) when compared with control group treated with Amoxicillin-Sulbactum. The study was conducted from September 2015 through December 2017 on lactating buffaloes suffering from clinical mastitis (n=307) (Treatment group, T1 = 156 and Control group, T2 = 151) mostly at farmer’s doorstep and also the participation of organized buffalo herds located at Hisar (n=2), Sirsa (n=1) from Haryana and at Nabha (n=1) from Punjab after follow up 1 and 2 at day 10 and 21 respectively. Infected quarters in Grade I and II lactation CM Treatment group (T1) were treated from day 0 to day 4 i.e. for 5 consecutive days with Ceftiofur hydrochloride IMM formulation or in Grade III lactation CM, IMM Ceftiofur hydrochloride along with parenteral Cefoperazone/Sulbactum. Control group (T2) received treatment from day 0 to day 2 i.e. for 3 consecutive days with Amoxicillin-Sulbactum antibiotic. Of 307 buffaloes infected with CM at day 0 pre-treatment, 93.49% of milk samples came culture positive whereas 52.12% (n=160/307) and 29.64% (91/307) of culture positive milk samples were there at day 10 and day 21 post-treatment respectively. Coagulase-negative Staphylococcus was the most prevalent causative agent followed by other gram positive, mixed infection, Escherichia coli, Staphylococcus aureus, Streptococcus spp, other coliform, Pseudomonas, other gram negative and Enterococcus spp. While apparent bacteriological cure rate of IMI was 50.37% (at animal level) at day 10 post-treatment in the Treatment group receiving Spectramast LC, it was 77.78% at day 21 post-treatment in the same group. The bacteriological cure rate of 45.45% and 57.58% were observed at day 10 and day 21 post-treatment in Control group respectively. Buffaloes receiving Spectramast LC (Treatment group) were 1.12 times (at day 10) and 1.35 times (at day 21) more likely to cure than Control group. Treatment group showed numerically higher clinical and pathogen cure than control group.